Vitamin D deficiency in pediatric sickle cell disease patients without crisis – A cry to investigate it on priority - Khan, Shahida Aziz; Al Zughaibi , Torki; Khan, Sarah A. (International Journal of Health Sciences, 2024)
Objective: The alarming increase in vitamin D deficiency (VDD) has been shown to result in compounded risks of major health problems globally. As sickle cell disease (SCD) children are already health compromised, the co-morbidities escalate early in life, demanding an early detection, to minimize the adverse effects. This study determined vitamin D levels in children with SCD without a crisis to check for probable associations with inflammation and infections if any. Methods: SCD children aged 5–16 years, in a steady state, were enrolled in the study after taking necessary consent and ethical clearance. Hb, serum calcium, vitamin D, and high-sensitivity C-reactive protein (hsCRP) levels were analyzed. Results: VDD was seen in most of the children with SCD irrespective of gender and age. Males aged 5–10 years showed significance (P = 0.0375) with vitamin D and white blood cell (WBC) (P = 0.0015) but males aged 11–16-year age group exhibited a very strong-positive correlation with vitamin D (r = 0.9862) and a very strong-negative correlation with Hb (r = −0.9819) and hsCRP (r = −0.9907). Among females, the 11–16-year age group patients exhibited a significant association with vitamin D (P = 0.0487), Ca (P = 0.0118), Hb (P = 0.0007), and hsCRP (P = 0.0001) levels. Correlation “r” values in this age group show a strong-negative correlation with WBC levels (r = −0.6525) as well as hsCRP (r = − 0.6550). Conclusion: The increased deficiency of vitamin D in SCD children should be addressed at early ages of life, to reduce the occurrence and severity of associated comorbidities.